Sistema de tratamento de água subterrânea em áreas rurais para abastecimento humano com filtração lenta não convencional - Rocha Júnior, Fernando Rodrigues da (2024)
Water supply systems depend on infrastructures both for distribution and for the treatment of raw water. While urban areas have significant demands for water for human consumption, rural areas tend to have demands for isolated distribution networks, due to the greater spacing between households. As a result, rural populations have lower coverage in water distribution compared to urban populations, exposing them to risks related to consuming water of suboptimal quality. Therefore, the use of individual water treatment techniques, such as slow filtration, serves as an alternative that enables the consumption of high-quality water without the need for the construction of long distribution networks. The decline in the quality of available raw water drives research into filtering materials that efficiently remove specific pollutants. In this context, the present study analyzed the use of sururu shells (Mytella guyanensis), a byproduct from the mollusk trade, as an unconventional filtering medium in three of four pilot filters used for the treatment of groundwater. One of the devices used only sand (conventional filter) to compare the quality of filtered water with and without the use of shells. The shells were subjected to different cleaning treatments, through ultrasonic bath (UB) and sun exposure (SE), and confined with the sand, which was also used as a conventional filtering medium in the filters. Scanning Electron Microscopy (SEM), Surface Area Analysis (BET), and X-ray Diffraction (XRD) tests were conducted to characterize the shells. To evaluate the efficiency of the treatments, the results were compared to the drinking water standards established by Ministry of Health Ordinance No. 888/2021, based on the following parameters: apparent color, turbidity, pH, hardness, aluminum, total iron, total coliforms, and thermotolerant coliforms. The results showed that the shells have a heterogeneous morphology with the presence of pores, classifying them as mesoporous material. The diffractograms identified calcite and ferrite phases in the shells. These findings explain the increase in hardness in filters with shell usage. Despite reducing color and turbidity parameters, the results still exceeded the maximum permissible values (MPV), with maximum efficiencies of approximately 45%. The pH of the filtered samples was more significant when compared to raw water, but without statistical evidence of the shells' influence. The removal of total iron and aluminum reached approximately 89%, with the shell-filled filters being more efficient in removing aluminum than the conventional filter. The removal of total coliforms was above 90%, and thermotolerant coliform removal reached 100%, although there was no statistical evidence of the influence of the shell usage or the material treatment. Therefore, although it was possible to assess the compliance of the filtered water with the drinking water ordinance, further studies are necessary with the use of the material in larger proportions and with a higher filtering medium height for a better analysis of the influence and applicability of sururu shells.